Diverging Attitudes in 2024 Indonesian Election Coverage: The Jakarta Post vs. Independent Observer - Khoirina Muqtafia; Widhiyanto; Henrikus Joko Yulianto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aimed to explore the utilization of attitudes in editorial articles about the 2024 Indonesian presidential election in The Jakarta Post and Independent Observer. Using a descriptive qualitative method, this study adopts the APPRAISAL theory by Martin & White, (2005) and Martin & Rose (2007) to analyze and interpret the evaluative language employed in the articles. The data were taken from editorial articles related to the 2024 Indonesian presidential election published in The Jakarta Post and Independent Observer from the end of 2023 to early 2024. This study employs textual and discourse analyses to examine the interpersonal language used and its broader social implications. The findings revealed that Appreciation is the most frequent category with 251 items (66%), followed by Judgment with 96 items (25%), and Affect with 33 items (9%). These findings indicate that the appreciation portrays the media's role in subtly guiding the audience's evaluation of political events, allowing for a space where audiences can form their own interpretations while still being subtly influenced by the media's tone. The judgment values used in the media imply that the media contributes to crafting a more competent and trustworthy image of politicians, which can influence the way voters view and assess them. Finally, the negative effect, especially insecurity, illustrates how the media may amplify doubts or fears related to the feasibility of government programs, which could influence public opinion and perception of political candidates. Furthermore, this study serves as a valuable reference for future researchers interested in media discourse analysis, particularly in the context of political journalism.